2012
DOI: 10.1016/j.neuroimage.2012.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Delayed monitoring of accuracy errors compared to commission errors in ACC

Abstract: Error detection is essential for monitoring performance and preparing subsequent behavioral adjustments, and is associated with specific neural responses in the anterior cingulate cortex (ACC). To investigate whether different brain mechanisms subserve the processing of commission vs. accuracy errors, we recorded EEG in adult participants while they performed a novel speeded GO-NOGO aiming task ("the Shoot-NoShoot paradigm"). Our ERP results show that commission errors (responding during NOGO trials) elicited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 92 publications
(120 reference statements)
2
15
0
Order By: Relevance
“…The temporal profile of the haptic interface execution error related ERP in a 3D motion task resembles classical ErrP (of conceptual errors and not motion errors), which is also characterized by a sharp negative peak, known as ERN or FRN, and a broader positive peak, known as Pe [9,10]. ErrPs in 2D continuous non-haptic motion task were characterized by four peaks [8], similar to our results in the 3D task.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The temporal profile of the haptic interface execution error related ERP in a 3D motion task resembles classical ErrP (of conceptual errors and not motion errors), which is also characterized by a sharp negative peak, known as ERN or FRN, and a broader positive peak, known as Pe [9,10]. ErrPs in 2D continuous non-haptic motion task were characterized by four peaks [8], similar to our results in the 3D task.…”
Section: Discussionsupporting
confidence: 83%
“…Feedback related negativity (FRN) is variation of ERN, evoked by presentation of feedback on incorrect action, and differs by latency range of 150-300 ms [10]. ERN of low amplitude can also be observed in trials with correct responses [9].…”
Section: Introductionmentioning
confidence: 99%
“…This study showed enhanced firing in a large number of MFC neurons during observed errors compared to observed correct actions of another monkey, as well as during reward delivery to the other monkey (Yoshida et al, 2012). Interestingly however, most of these neurons did not respond to self-generated errors, indicating parallel but separate neural populations for the monitoring of self-and other-generated actions (Yoshida et al, 2012 Koban et al, 2012). These authors demonstrated activation of dMFC for errors compared to hits independent of context, whereas the ventral striatum responded as a function of the subjective reward value of errors vs. hits (higher striatum activation for hits in cooperation, and for errors in competition).…”
Section: Monitoring and Evaluating The Actions Of Othersmentioning
confidence: 64%
“…FMRI results indicate that the dorsomedial prefrontal cortex shows higher activation during error monitoring in social relative to individual settings (Radke et al, 2011). In a recent ERP study, Koban et al (2012) showed that the FRN was increased in cooperative compared to competitive context, with underlying sources in the dorsomedial PFC, LPFC, and temporoparietal junction (TPJ), all these regions being typically involved in social cognition (see Figure 2, and cf. Kelley et al, 2002;Mitchell et al, 2005;Saxe and Wexler, 2005).…”
Section: Social Influences On the Monitoring Of Self-generated Actionsmentioning
confidence: 97%
“…Monitoring is mainly based on internal representation of own or observed motor action, when the information about the correctness or goal conduciveness of a given action is available already at the time of or even before the onset of the motor response. On the other hand, monitoring has to rely on external feedback when there is no reliable internal knowledge about the correctness or incorrectness at the time of action execution (Holroyd & Coles, 2002;(Bediou, Koban, Rosset, Pourtois, & Sander, 2012). When both types of information are available, later occurring external feedback might be redundant and low in predictive relevance, and thus not elicit a prediction error signal (Heldmann, et al, 2008;Holroyd & Coles, 2002).…”
Section: Effects Of Social Context and Predictive Relevance On Actionmentioning
confidence: 99%